2021
DOI: 10.1080/09286586.2021.1962919
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Herpes Simplex Virus Keratitis and Other Ocular Disease: Global Review and Estimates

Abstract: Purpose: We aimed to review available data on the incidence of herpes simplex virus (HSV) keratitis and other HSV ocular disease and to estimate the global burden of HSV ocular disease. Methods: We searched Medline and Embase databases to October 2020 for studies reporting on the incidence of HSV ocular disease. Study quality was evaluated using a four-point checklist. Pooled estimates were applied to 2016 population data to estimate global HSV ocular disease burden. Numbers with uniocular vision impairment (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Herpes Simplex Virus type 1 (HSV-1) and type 2 (HSV-2) cause lifelong infections with periodic reactivations that are highly prevalent worldwide [ 198 , 199 ]. A wide range of diseases result from HSV infections, from the most common cold sores and genital herpes, to recurrent keratitis, and even life-threatening systemic infections and encephalitis [ 198 , 199 ]. Antiviral intervention is therefore needed for the therapy of these diseases.…”
Section: The Broad-spectrum Antiviral Activity Of A-type Pacsmentioning
confidence: 99%
“…Herpes Simplex Virus type 1 (HSV-1) and type 2 (HSV-2) cause lifelong infections with periodic reactivations that are highly prevalent worldwide [ 198 , 199 ]. A wide range of diseases result from HSV infections, from the most common cold sores and genital herpes, to recurrent keratitis, and even life-threatening systemic infections and encephalitis [ 198 , 199 ]. Antiviral intervention is therefore needed for the therapy of these diseases.…”
Section: The Broad-spectrum Antiviral Activity Of A-type Pacsmentioning
confidence: 99%
“… 7 As the 2nd leading cause of blindness in the developed world, herpetic keratitis was estimated to cause newly acquired vision impairment in 230,000 people worldwide in 2016. 18 Previous studies have found several risk factors which may induce the reactivation of ocular HSV in humans and animal models, including eye surgery, ultraviolet exposure, latanoprost, topical steroids, and immunocompetent state. Therefore, patients with a history of herpetic eye diseases should be carefully evaluated before any eye surgeries, including corneal crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…HSV keratitis has been recognized as the frequent cause of corneal blindness or severe mononuclear visual impairment, affecting nearly 1.5 million people worldwide [ 185 ]. Drug-loaded liposome formulation can be dispersed as patient-friendly ophthalmic drops for the therapy of different ocular disorders.…”
Section: Nanocarriers In Ocular Drug Deliverymentioning
confidence: 99%